HUBUNGAN USIA DAN INDEKS MASSA TUBUH DENGAN VO2MAX PADA PEMAIN BASKET DI MATARAM BASKETBALL SCHOOL DAN BIMA PERKASA ACADEMY: HUBUNGAN USIA DAN INDEKS MASSA TUBUH DENGAN VO2MAX - Rizky Wulandari (Jurnal Ilmiah Fisioterapi, 2023)
Background: In sports activities, athletes must have a good VO2Max level. VO2Max is the highest oxygen consumption rate that can be achieved during maximal or submaximal exercise. Basically VO2Max is influenced by several factors, such as age and body mass index (BMI). Research Objectives: To determine the relationship between age and body mass index with VO2Max in basketball players at Mataram Basketball School and Bima Perkasa Academy. Research Methods: The methodology used for this research is cross-sectional with a quantitative approach. The total sampling technique is used as the sampling method. The subjects of this study were basketball players aged 13-18 years at Mataram Basketball School and Bima Perkasa Academy. VO2Max measurements using the Cooper Test and measurements of weight, height and age seen from player profile data. Research results: The results of the correlation test with the Pearson test between age and VO2Max obtained a value of p = 0.017 (p <0.05), while between Body Mass Index and VO2Max, it was p = 0.025 (p <0.05). Conclusion: There is a relationship between age and body mass index with VO2 max in basketball players at Mataram Basketball School and Bima Perkasa Academy. Suggestion: Respondents are advised to maintain their diet and pay attention to body mass index, measure body mass index and VO2Max regularly, and it is hoped that future researchers can conduct research on other factors that affect VO2Max